Kadar amonia dan urea darah bayi prematur pada usia minggu pertama - Purnomo Suryantoro Purnomo Suryantoro (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1996)
Ammonia and urea blood levels in premature infants during the first week of life were analyzed. Twenty seven blood samples from premature infants at the age of 1, 3 and 7 days were collected. The concentration of ammonia was determined using Amitest meter (TSUGAI), while the urea concentration was measured using regular techniques. Even though the ammonia levels did not exceed 180 pg/d1., the data showed that the critical situation occur in the first three days of life when the ammonia concentration was the highest and urea was also concentrated. This condition releaved in day seven.Key words : ammonia level - urea level - premature baby - enzyme deficiency - hyperammonemia